2004
DOI: 10.1177/1359105304036104
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Determinants of Premature Health Deterioration in a Changing Society: The Case of Hungary

Abstract: The drastic increase of morbidity and mortality rates in the transforming Central-Eastern European countries, characterizing the last decades, offers a unique opportunity to analyse the relationship of those social, psychological and biological processes that contribute to rapid health modifications. In 1988 and 1995, two national representative surveys of the Hungarian population aged 16 or older (N = 20,902 and 12,640 respectively) were conducted. The results show that depressive symptom severity mediates be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…This is unfortunate, since there is a high prevalence of job instability and unemployment and a strong association with adverse health in some Central and Eastern European countries, particularly Hungary. 23 When comparing Eastern with Western Europe, it should be stressed that unemployment at the time of data collection was relatively high in several Western countries including Germany. Further analysis of the Heinz Nixdorf Study found that the risk of poor health was highest in the subgroup of employees who had a low occupational status (and unstable jobs) and who exhibited a high level of psychosocial stress at work.…”
Section: Discussionmentioning
confidence: 99%
“…This is unfortunate, since there is a high prevalence of job instability and unemployment and a strong association with adverse health in some Central and Eastern European countries, particularly Hungary. 23 When comparing Eastern with Western Europe, it should be stressed that unemployment at the time of data collection was relatively high in several Western countries including Germany. Further analysis of the Heinz Nixdorf Study found that the risk of poor health was highest in the subgroup of employees who had a low occupational status (and unstable jobs) and who exhibited a high level of psychosocial stress at work.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding microsystems as workplaces, low control at work and depression was found to be a mediator between general morbidity and mortality and the majority of risk consequences of a low socioeconomic situation among men in two national representative surveys of the Hungarian population conducted in 1988 and 1995 (Kopp et al., 2004). Nevertheless, the imbalance of effort–reward at work (which could be considered an “objective” measure of working conditions) but not job control (which could be considered a measure of subjective control) was associated with depressive symptoms and increased alcohol intake and problem drinking in a transnational study in three Eastern European urban populations (Bobak et al., 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The significantly higher HR in Hungarian respondents further supports the notion of increased sympatho-adrenergic activity in this group. Recent national surveys also report that psychosocial determinants contribute to increased morbidity and mortality in Hungary [31,32].…”
Section: Cross-national Blood Pressure Comparisonmentioning
confidence: 94%